Adolescent subgenual anterior cingulate activity is related to harm avoidance - Yang, Tony T. (2009)
Recent adult studies suggest that the subgenual anterior cingulate cortex (sgACC) is involved in fundamental mental operations such as affective processing and inhibitory control. However, little is known about inhibition-associated sgACC function in adolescents, and there are no published data regarding whether personality characteristics are related to inhibition-associated sgACC brain activity in adolescents. This study examined the relationship between personality and inhibition-associated sgACC response in healthy adolescents. Seventeen adolescents of 13–17 years of age underwent functional magnetic resonance imaging while performing a parametric stop-signal task. Greater harm avoidance levels were significantly associated with increased inhibition-related sgACC activity. These results establish, for the first time, a link between personality and differential sgACC activation in adolescents.